Coping with stress and quality of life in women with stress urinary incontinence - Adamczuk, Jolanta; Szymona-Pałkowska, Katarzyna; Robak, Jacek Marcin; Rykowska-Górnik, Katarzyna; Steuden, Stanisława; Kraczkowski, Janusz Jacek (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: Urinary incontinence (UI) involves uncontrolled leakage of urine through the urethra as a result of damage to its sphincter muscle and a disturbed function of the urogenital diaphragm within the pelvis minor. The symptoms of UI radically impair psychological, somatic, and social functioning. The aim of each disease stress coping process is to reduce the impact of harmful agents as well as the acquisition of necessary preventive measures in order to combat the disorder. Aim of the study was to assess the relationship between coping styles used when dealing with stress associated with disease and the quality of life. Material and methods: The study was carried out at an outpatients’ clinic located in the Lublin Province (eastern Poland), covering 150 women with diagnosed stress urinary incontinence, aged between 32 and 79. The following methods were used: (a) Coping Inventory for Stressful Situations (Endler, Parker) to assess coping styles, (b) CASP-19 scale (Higgins, Hyde, Wiggins, Blade) to measure the overall quality of life, and (c) Urinary Incontinence Life Quality Scale (Szymona-Pałkowska, Kraczkowski). Results : The preferred style in the studied group of women was Task-Oriented Coping. This style is associated with a low score on the Independence from Symptoms scale and low Control, being simultaneously correlated with Autonomy and Self-Realisation. Emotion-Oriented Coping is associated with low psychological, physical and social well-being, as well as with little independence from the disease symptoms, little pleasure and self-realisation, but it gives a sense of internal control. Avoidance-Oriented Coping does not significantly correlate with any of the Overall Quality of Life dimensions. Conclusions : Women suffering from UI tend to try to solve their problem by means of cognitive transformation. In their situation, clinging to the problem turns out to be a depressing factor and entails a lower quality of their life.